FAKTOR KEUANGAN YANG MEMPENGARUHI RENTABILITAS MODAL SENDIRI: STUDI PADA INDUSTRI BAHAN KIMIA - Nuryani, Nanda Alfa; Kristiana, Deranika Ratna (LPPM STIE YKPN Yogyakarta, 2024)
The Indonesian economy and companies in this industrial sector are related in terms of profitability of own capital, therefore this study uses the title of financial factors that affect profitability of own capital. These financial factors include capital structure, liquidity, company size, company age, equity multiplier, as well as capital turnover efficiency. In this study using the classical assumption test and also multiple linear regression analysis in which the classic assumption test used is normality, multicollinearity, heteroscedasticity, and autocorrelation test. As well as multiple linear regression analysis, there are r-square tests, simultaneous test, and hypotheses. The sampling technique was purposive sampling with data from 40 companies which obtained the result that the data in this study were normally distributed, there was no multicollinearity, there were no heteroscedasticity problems, and there were no autocorrelation problems. The conclusion is that all independent variables (financial factors) namely capital structure, liquidity, company size, company age, equity multiplier, as well as capital turnover efficiency have a positive effect on earnings own capital.